Humanistic Learning Approach in Internalizing Students' Character in Elementary Schools - Nour Ariyanti Amir; Syamsu Kamaruddin; Abdullah Sinring; Lutfi Lutfi (DIDAKTIKA, 2024)
Humanistic learning is an approach that emphasizes the importance of individual student experiences and moral values in the learning process. Therefore, this research aims to identify the effectiveness of the humanistic learning approach in internalizing students' character in elementary schools, with a focus on the impact of teaching methods on the development of students' attitudes and character behaviors. In elementary education, character internalization is crucial for building a foundation of positive attitudes and behaviors. The results of this approach indicate that students engaged in humanistic learning tend to show improvements in character aspects, such as honesty, discipline, and a positive attitude towards school. Additionally, they are also better able to face social challenges in their environment. By internalizing good character, it is hoped that students will not only become high-achieving individuals but also be able to contribute positively to society and their surroundings. This research highlights the need for the integration of a humanistic approach in the education curriculum, in order to optimize the formation of strong character among the younger generation, as well as to encourage best practices in education that are oriented towards the holistic development of children.